Modified organic silicon resin and preparation method thereof as well as organic silicon optical cement and application thereof

Through the preparation of modified silicone resin and the use of organic silicon compounds containing mercapto and alkoxy groups for blending and grafting, the stability problem of existing optical glue at low and high temperatures is solved, and the display clarity of the display screen is improved. degree and environmental adaptability.

CN119351049AActive Publication Date: 2025-01-24CROWN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411600248.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The optical glue of existing touch displays is prone to lose stickiness or shrinkage at low temperatures, has poor durability at high temperatures, and is prone to oxidation and yellowing under ultraviolet irradiation, affecting the display clarity.

Method used

Using modified silicone resin, by adding thiol- and alkoxy-containing silicone compounds as modifiers to methyl MQ resin and epoxy-modified MQ resin, blending and grafting are performed, dehydroxylation is performed and compatibility is improved. properties, thereby preparing silicone optical glue with excellent optical properties.

Benefits of technology

It achieves the stability of silicone optical glue under high and low temperatures, improves the characteristics of low initial peeling force and high creep in the later stage, facilitates repair, and improves the display clarity and environmental adaptability of the display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128663040000031
    Figure BDA0005128663040000031
  • Figure BDA0005128663040000101
    Figure BDA0005128663040000101
  • Figure BDA0005128663040000111
    Figure BDA0005128663040000111
Patent Text Reader

Abstract

The invention provides modified organic silicon resin. The modified organic silicon resin comprises methyl MQ resin, epoxy modified MQ resin, a modifier, a basic catalyst, a first solvent and a second solvent, wherein the M / Q ratio of the methyl MQ resin is 0.55 to 0.75, and the M / Q ratio of the epoxy modified MQ resin is 0.7 to 0.9; the epoxy value of the epoxy modified MQ resin is 0.06 to 0.16 percent; the modifier is an organosilicon compound containing sulfydryl and alkoxy. The organic silicon optical adhesive prepared from the modified organic silicon resin provided by the invention has excellent optical performance, high and low temperature modulus, elongation at break and peeling strength, can realize the characteristics of low initial peeling force and high later-stage climbing, is convenient for timely repair in practical application, has excellent solid pasting effect and die cutting effect, and is suitable for large-scale production. And the coating is convenient in process, and the large-batch production requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a modified silicone resin and a preparation method thereof, a silicone optical adhesive and applications thereof. Background Art

[0002] With the display function and the convenience of touch function of touch screen, its development speed and application scope have been rapidly improved in recent years; but at the same time, higher requirements are also put forward for its quality. On the basis of meeting its functional application, it is also necessary to improve its adaptability to the environment and the stability of quality.

[0003] At present, most acrylic optical adhesives used in the market are used for the bonding of touch screens. They can be used in conventional environments and have good bonding effects. However, due to its relatively high glass transition temperature (Tg), it is easy to lose adhesion or shrink at low temperatures, resulting in abnormal display or touch of the touch screen at low temperatures; moreover, its high temperature resistance is poor, and cohesive failure often occurs at high temperatures, resulting in displacement of the glass cover plate bonded to the display screen, causing abnormal touch; in addition, if the display screen is exposed to ultraviolet rays for a long time outdoors, it is easy to oxidize and turn yellow, affecting the display color and clarity of the display screen. In the prior art, silicone optical adhesives are also used for the bonding of display screens, but their stability is poor, and they are prone to problems such as excessive hardness and abnormal exhaust properties. Moreover, their initial bonding peeling force is basically the same as the peeling force after standing for 72 hours. When the initial bonding is poor and needs to be repaired, the peeling force is high and it is not easy to operate; in addition, the current silicone optical adhesive has a low refractive index and the display clarity needs to be improved.

[0004] In summary, based on the above technical problems, it is necessary to develop an optical adhesive for touch screens with better performance. Summary of the invention

[0005] In view of the above, the present invention provides a modified silicone resin and a preparation method thereof, a silicone optical adhesive and an application thereof. The silicone optical adhesive prepared by the modified silicone resin provided by the present invention has excellent optical properties, high and low temperature modulus, high elongation at break and peel strength, excellent solid pasting effect and die-cutting effect, and can achieve the characteristics of low initial peeling force and high later climbing force, which is convenient for timely repair.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a modified silicone resin, comprising the following components: methyl MQ resin, epoxy modified MQ resin, a modifier, an alkaline catalyst, a first solvent and a second solvent;

[0008] Wherein, the M / Q ratio of the methyl MQ resin is 0.55 to 0.75, and the M / Q ratio of the epoxy modified MQ resin is 0.7 to 0.9;

[0009] The epoxy value of the epoxy-modified MQ resin is 0.06 to 0.16%;

[0010] The modifier is an organic silicon compound containing a mercapto group and an alkoxy group.

[0011] The second aspect of the present invention provides a method for preparing the modified silicone resin according to the first aspect of the present invention, the method comprising the following steps:

[0012] The methyl MQ resin, the epoxy modified MQ resin, the modifier, the alkaline catalyst, the first solvent and the second solvent are mixed according to the above ratio and stirred evenly; after nitrogen is introduced, the mixture is heated to 80-120° C. and maintained for 6-10 hours until it reacts to a transparent liquid; the transparent liquid is rotary evaporated at 140-180° C. and a vacuum pressure of -0.1 MPa to -0.05 MPa for 2-6 hours, and the modified silicone resin is obtained after the temperature is reduced and the pressure is increased to normal temperature and pressure.

[0013] The third aspect of the present invention provides an organic silicone optical adhesive, which comprises the following components in parts by weight:

[0014]

[0015] Wherein, the modified silicone resin is the modified silicone resin described in the first aspect of the present invention or the modified silicone resin prepared by the method described in the second aspect of the present invention.

[0016] The fourth aspect of the present invention provides an application of an organic silicone optical adhesive, wherein the organic silicone optical adhesive described in the third aspect of the present invention is applied to the bonding of a touch display screen.

[0017] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0018] (1) The modified silicone resin provided by the present invention can be blended and grafted with methyl MQ resin and epoxy modified MQ resin under the catalysis of an alkaline catalyst by using an organosilicon compound containing a mercapto group and an alkoxy group as a modifier to achieve dehydroxylation in the composition. At the same time, due to the introduction of organic groups, the compatibility of the modified silicone resin with other silicone oils can be effectively improved, thereby increasing the refractive index and light transmittance of the product to improve the display clarity;

[0019] (2) The epoxy groups contained in the modified silicone resin and the alkoxy groups in the modifier provided by the present invention can react with active groups such as hydroxyl groups on the surface of the adhered object or form hydrogen bonds, so that the peeling force of the silicone optical adhesive will slowly increase after 24 hours, thereby achieving the characteristics of low initial peeling force and high later climbing force, which is convenient for timely repair.

[0020] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. DETAILED DESCRIPTION

[0021] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0022] The first aspect of the present invention provides a modified silicone resin, comprising the following components: methyl MQ resin, epoxy modified MQ resin, a modifier, an alkaline catalyst, a first solvent and a second solvent;

[0023] Wherein, the M / Q ratio of the methyl MQ resin is 0.55 to 0.75, and the M / Q ratio of the epoxy modified MQ resin is 0.7 to 0.9;

[0024] The epoxy value of the epoxy-modified MQ resin is 0.06 to 0.16%;

[0025] The modifier is an organic silicon compound containing a mercapto group and an alkoxy group.

[0026] Under the catalysis of an alkaline catalyst, the methyl MQ resin and the epoxy modified MQ resin in the modified silicone resin are blended and grafted with a modifier of an organosilicon compound containing a mercapto group and an alkoxy group, thereby achieving dehydroxylation in the composition. Since the hydroxyl group is a polar functional group, its presence will cause a strong interaction between the silicone composition and the silicone oil and other components in the adhesive component, reducing their compatibility. By dehydroxylation, this interaction can be reduced, so that the organic groups in the methyl MQ resin and the epoxy modified MQ resin can be smoothly connected to other components of the optical adhesive, thereby improving the modified silicone resin and the organic The compatibility of silicone oil and other ingredients in silicone optical adhesive improves the optical properties of silicone optical adhesive, increases the refractive index and transmittance of the product, and improves the clarity of the display screen; in addition, the mercapto and alkoxy groups contained in the modifier can undergo a grafting reaction with the silanol groups in the silicone resin under the action of a catalyst to form a resin containing mercapto and alkoxy groups. During the addition reaction of the optical adhesive, the mercapto group participates in a partial silylation reaction to form an S-Si bond. Since the new chemical bond has a higher polarity than the original siloxane bond, it also increases the dielectric constant of the adhesive film after cross-linking and curing. Therefore, the refractive index of the silicone optical adhesive can be further improved.

[0027] Further, according to the optical silicone composition of the present invention, the M / Q ratio of the methyl MQ resin is 0.55 to 0.75. For example, the M / Q ratio of the methyl MQ resin can be 0.55, 0.6, 0.65, 0.7, 0.75, or any value between the two values; the M / Q ratio of the epoxy-modified MQ resin is 0.7 to 0.9. For example, the M / Q ratio of the epoxy-modified MQ resin can be 0.7, 0.75, 0.8, 0.85, 0.9, or any value between the two values. The M / Q ratios of the methyl MQ resin and the epoxy-modified MQ resin represent the monofunctional siloxane chain segments (R3SiO 1 / 2 , i.e. M) and tetrafunctional siloxane chain (SiO 4 / 2 By controlling the M / Q ratio of methyl MQ resin and epoxy-modified MQ resin, the monofunctional siloxane chain segment (R3SiO 1 / 2 , i.e. M) and tetrafunctional siloxane chain (SiO 4 / 2 , i.e. the relative number of Q), thereby avoiding excessive or insufficient siloxane bonds. On the one hand, it can enable the modified silicone resin to form a more stable grafted structure and improve its thermal stability; on the other hand, it can avoid excessive siloxane bonds leading to a deterioration in the polarity of the modified silicone resin, thereby affecting the refractive index, transmittance and haze of the product.

[0028] In a specific embodiment, the weight average molecular weight of the methyl MQ resin is 6,000 to 9,000 g / mol, and can be 6,000 g / mol, 6,500 g / mol, 7,000 g / mol, 7,500 g / mol, 8,000 g / mol, 8,500 g / mol, 9,000 g / mol, or any value between the two end values. By controlling the weight average molecular weight of the methyl MQ resin within a suitable range, the modified silicone resin can obtain a higher viscosity and mechanical strength, thereby improving the elongation at break of the optical adhesive, and also improving the high and low temperature stability of the optical adhesive and improving its environmental adaptability.

[0029] In a specific embodiment, the hydroxyl content of the methyl MQ resin is 1.3-2.5%; illustratively, it can be 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, or any value in between.

[0030] Exemplarily, the mass range of the methyl MQ resin in the modified silicone resin is 30 to 60 parts by weight, specifically 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, 42 parts by weight, 44 parts by weight, 46 parts by weight, 48 parts by weight, 50 parts by weight, 51 parts by weight, 53 parts by weight, 55 parts by weight, 57 parts by weight, 59 parts by weight, 60 parts by weight, or any value between the two end values.

[0031] Further, the epoxy value of the epoxy-modified MQ resin is 0.06-0.16%. For example, the epoxy value of the epoxy-modified MQ resin can be 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, or any value between the two end values. The epoxy value represents the number of epoxy group links. The epoxy group is a type of polar reactive active group that can react with thiol and hydroxyl groups, and can also form hydrogen bonds with active hydrogen atoms. These interactions can further enhance the adhesion and mechanical strength of the adhesive, thereby improving the peel strength.

[0032] In a specific embodiment, the weight average molecular weight of the epoxy-modified MQ resin is 4,000 to 7,000 g / mol. For example, it can be 4,000 g / mol, 4,500 g / mol, 5,000 g / mol, 5,500 g / mol, 6,000 g / mol, 6,500 g / mol, 7,000 g / mol, or any value in between.

[0033] In a specific embodiment, the hydroxyl content of the epoxy modified MQ resin is 0.3-1%. For example, the hydroxyl content of the epoxy modified MQ resin can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or any value between the two end values. The hydroxyl content directly affects the chemical reactivity of the methyl MQ resin and the epoxy modified MQ resin. Resins with higher hydroxyl content are more likely to react chemically with other compounds, including modifiers and catalysts added to the optical silicone composition. However, if the hydroxyl content of the resin is too high, the compatibility of the modified silicone resin will be poor; if the hydroxyl content is too low, the degree of resin reaction will be insufficient.

[0034] In addition, the test method for the hydroxyl content in the methyl MQ resin and the epoxy-modified MQ resin in the present invention adopts a reaction gas volume method, which mainly uses lithium aluminum hydride to react with the silanol groups in the methyl MQ resin or the epoxy-modified MQ resin to generate hydrogen, uses a level bottle to collect and measure the volume of the generated hydrogen, and calculates the hydroxyl content based on the volume of the hydrogen.

[0035] Exemplarily, the mass range of the epoxy-modified MQ resin in the modified silicone resin is 10 to 20 parts by weight, specifically 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, or any value between the two ends.

[0036] Furthermore, the modifier is an organic silicon compound containing a mercapto group and an alkoxy group, and the alkoxy group includes one or both of a methoxy group and an ethoxy group.

[0037] The epoxy groups contained in the modified silicone resin provided by the present invention and the alkoxy groups contained in the modifier can react or form hydrogen bonds with active groups such as hydroxyl groups on the surface of the adhered object after a certain period of time, so it can be ensured that the peeling force of the silicone optical adhesive provided by the present invention slowly increases after 24 hours, thereby achieving the characteristics of low initial peeling force and high later climbing force, which is convenient for timely repair.

[0038] In a specific embodiment, the content of the mercapto group in the modifier is 5.5-8.7%, and the content of the alkoxy group is 22.36-49.47%.

[0039] In a specific embodiment, the modifier includes at least one of 3-mercaptopropyltrimethoxysilane, 11-mercaptoundecyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and γ-mercaptopropyltriethoxysilane.

[0040] Exemplarily, the mass range of the modifier in the modified silicone resin is 8 to 18 parts by weight, specifically 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, or any value between the two ends.

[0041] In a specific embodiment, the alkaline catalyst includes at least one of tetramethylammonium hydroxide pentahydrate and potassium hydroxide. They are strong bases and can catalyze organosilicon to break alkoxy groups and condense with hydroxyl groups at low doses. Tetramethylammonium hydroxide pentahydrate is preferred for catalysis, which is convenient for subsequent decomposition and removal.

[0042] Exemplarily, the mass range of the alkaline catalyst in the modified silicone resin is 0.05 to 0.3 parts by weight, specifically 0.05 parts by weight, 0.06 parts by weight, 0.07 parts by weight, 0.08 parts by weight, 0.09 parts by weight, 0.1 parts by weight, 0.12 parts by weight, 0.14 parts by weight, 0.16 parts by weight, 0.18 parts by weight, 0.2 parts by weight, 0.21 parts by weight, 0.23 parts by weight, 0.25 parts by weight, 0.27 parts by weight, 0.29 parts by weight, 0.3 parts by weight, or any value between the two ends.

[0043] In a specific embodiment, the first solvent includes at least one of anhydrous ethanol, methanol, and isopropanol. The first solvent is used to dissolve the alkaline catalyst so that the alkaline catalyst can be better mixed with other components to promote the reaction.

[0044] Exemplarily, the mass range of the first solvent in the modified silicone resin is 0.3 to 1 part by weight, specifically 0.3 part by weight, 0.4 part by weight, 0.5 part by weight, 0.6 part by weight, 0.7 part by weight, 0.8 part by weight, 0.9 part by weight, 1 part by weight, or any value in between.

[0045] In a specific embodiment, the second solvent includes at least one of cyclohexane, heptane and octane. The second solvent can provide a reaction medium for the modification and grafting reaction of the above components, so that the components are mixed evenly and the reaction is carried out smoothly.

[0046] Exemplarily, the mass range of the second solvent in the modified silicone resin is 20 to 40 parts by weight, specifically 20 parts by weight, 22 parts by weight, 24 parts by weight, 26 parts by weight, 28 parts by weight, 30 parts by weight, 31 parts by weight, 33 parts by weight, 35 parts by weight, 37 parts by weight, 39 parts by weight, 40 parts by weight, or any value between the two ends.

[0047] According to the modified silicone resin of the present invention, the proportions of the components in the modified silicone resin are as follows, in parts by weight:

[0048]

[0049] The second aspect of the present invention provides a method for preparing the modified silicone resin according to the first aspect of the present invention, the method comprising the following steps:

[0050] The methyl MQ resin, the epoxy modified MQ resin, the modifier, the alkaline catalyst, the first solvent and the second solvent are uniformly mixed according to the above ratio; after nitrogen is introduced, the mixture is heated to 80-120° C. and maintained for 6-10 hours until it reacts to a transparent liquid; the transparent liquid is rotary evaporated at 140-180° C. and a vacuum pressure of -0.1 MPa to -0.05 MPa for 2-6 hours, and the modified silicone resin can be obtained after the temperature is reduced and the pressure is increased to normal temperature and pressure.

[0051] According to the method of the present invention, in the step, nitrogen is introduced into the material and then heated to 80-120°C, and maintained for 6-10 hours until it reacts to a transparent liquid; the heating temperature in the exemplary step can be 80°C, 90°C, 100°C, 110°C, 120°C, or any value between the two end values; the holding time can be 6h, 7h, 8h, 9h, 10h, or any value between the two end values. The temperature in this section is mainly the process of tetramethylammonium hydroxide catalytic reaction. This temperature and time are mainly for condensation grafting reaction of thiol, hydroxyl, and part of epoxy groups. If the temperature is too low, some reactions may not proceed and the time is too long. If the temperature is too high, some catalysts may decompose and fail, resulting in low reaction efficiency and low grafting rate.

[0052] According to the method of the present invention, in the step, the transparent liquid is rotary evaporated at 140-180°C for 2-6 hours, and the modified silicone resin is obtained after cooling and increasing the pressure to normal temperature and pressure. The rotary evaporation temperature in the exemplary step can be 140°C, 150°C, 160°C, 170°C, 180°C, or any value between the two end values; the rotary evaporation time can be 2h, 3h, 4h, 5h, 6h, or any value between the two end values; the rotary evaporation pressure can be -0.1MPa, -0.09MPa, -0.08MPa, -0.07MPa, -0.06MPa, -0.05MPa, or any value between the two end values. This temperature and pressure are mainly for thermal decomposition and vacuum extraction of the catalyst.

[0053] The third aspect of the present invention provides an organic silicone optical adhesive. The proportions of the components in the organic silicone optical adhesive are as follows, in parts by weight:

[0054]

[0055] Wherein, the modified silicone resin is the modified silicone resin described in the first aspect of the present invention or the modified silicone resin prepared by the method described in the second aspect of the present invention.

[0056] The modified silicone resin provided by the present invention is subjected to a dehydroxylation treatment, so that after the reaction, a mercapto- and alkoxy-containing silicone resin can be generated. The resin can react with a double-ended hydrogenated silicone oil and two different molecular weight vinyl silicone oils in an optical adhesive under a platinum catalyst and heating conditions to obtain an adhesive having a ring-type interlocking polysiloxane skeleton with a macromolecular chain, and stable control of its modulus, elongation and breaking strength is achieved, so that the silicone optical adhesive prepared by the present invention has the characteristics of excellent high and low temperature modulus, high elongation at break and low initial peel strength and subsequent high climbing strength.

[0057] In the present invention, the viscosity of the vinyl silicone oil A is 2,000 to 10,000 mPa.s. For example, it can be 2,000 mPa.s, 3,000 mPa.s, 4,000 mPa.s, 5,000 mPa.s, 6,000 mPa.s, 7,000 mPa.s, 8,000 mPa.s, 9,000 mPa.s, 10,000 mPa.s, or any value in between.

[0058] In the present invention, the vinyl content of the vinyl silicone oil A is 0.12-0.23%. For example, it can be 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, or any value between the two end values.

[0059] In the present invention, the content of the vinyl silicone oil A is 15 to 25 parts by weight. For example, it can be 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, or any value between the two ends.

[0060] In the present invention, the viscosity of the vinyl silicone oil B is 50,000 to 100,000 mPa.s. For example, it can be 50,000 mPa.s, 55,000 mPa.s, 60,000 mPa.s, 65,000 mPa.s, 70,000 mPa.s, 75,000 mPa.s, 80,000 mPa.s, 85,000 mPa.s, 90,000 mPa.s, 95,000 mPa.s, 100,000 mPa.s, or any value between the two ends.

[0061] The present invention can better control the high and low temperature modulus, breaking strength and peeling strength of the organic silicone optical adhesive by using two types of vinyl-terminated silicone oils with different molecular weights and different viscosities.

[0062] According to the organic silicone optical adhesive of the present invention, the vinyl content in the vinyl silicone oil B is 0.03-0.07%. For example, it can be 0.03%, 0.04%, 0.05%, 0.06% or 0.07%, or any value between the two end values.

[0063] The vinyl content in vinyl silicone oil A and vinyl silicone oil B can directly affect their reactivity. The terminal vinyl can form more silicon-carbon bonds during the cross-linking process and provide a basic network structure. Too much vinyl content will lead to a small molecular weight after cross-linking and affect the final tensile and compression properties of the product, which is manifested in the decrease in the increase in the bonding bubbles and peeling force when the film is used. However, too little vinyl content will lead to a slow cross-linking reaction or even an insufficient reaction, resulting in low cohesive strength and film stratification. Therefore, the present invention can effectively balance the stability of the cross-linking structure and the compatibility between the components by adjusting the vinyl content of the two vinyl silicone oils, and can generate a polysiloxane skeleton with a ring structure, thereby further improving the cross-linking stability of the optical adhesive.

[0064] In the present invention, the content of the vinyl silicone oil B is 30 to 40 parts by weight. Exemplarily, it can be 30 parts by weight, 31 parts by weight, 32 parts by weight, 33 parts by weight, 34 parts by weight, 35 parts by weight, 36 parts by weight, 37 parts by weight, 38 parts by weight, 39 parts by weight, 40 parts by weight, or any value between the two ends.

[0065] In the present invention, the content of the modified silicone resin is 15 to 25 parts by weight. Exemplarily, it can be 15 parts by weight, 16 parts by weight, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, or any value in between.

[0066] In the present invention, the inhibitor comprises at least one of vinyl ring body, alkynol and diallyl maleate. Alkynol is preferred, mainly because it has the advantages of excellent inhibition stability at room temperature, fast high temperature deactivation speed and fast product reaction.

[0067] In the present invention, the content of the inhibitor is 0.02 to 0.08 parts by weight, and illustratively, it can be 0.02 parts by weight, 0.03 parts by weight, 0.04 parts by weight, 0.05 parts by weight, 0.06 parts by weight, 0.07 parts by weight, 0.08 parts by weight, or any value in between.

[0068] In the present invention, the hydrogen content of the double-ended hydrogen-containing silicone oil is 0.04-0.08%, and can be 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, or any value in between.

[0069] In the present invention, the viscosity of the double-ended hydrogen-containing silicone oil is 300-700 mm 2 / s, for example, it can be 300mm 2 / s、350mm 2 / s、400mm 2 / s、450mm 2 / s、500mm 2 / s、550mm 2 / s、600mm 2 / s、650mm 2 / s、700mm 2 / s; or any value between the two values.

[0070] In the present invention, the content of the double-ended hydrogen-containing silicone oil is 3 to 8 parts by weight, and illustratively, it can be 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, or any value in between.

[0071] In the present invention, the hydrogen content of the hydrogen-containing silicone resin is 0.2-0.5%; illustratively, the hydrogen content of the hydrogen-containing silicone resin may be 0.2%, 0.3%, 0.4%, 0.5%, or any value in between.

[0072] In the present invention, the M / Q ratio of the hydrogen-containing silicone resin is 1.2 to 1.5. Exemplarily, the M / Q ratio of the hydrogen-containing silicone resin may be 1.2, 1.3, 1.4, 1.5, or any value in between.

[0073] In the present invention, the viscosity of the hydrogen-containing silicone resin is 500-1,500 mPa.s. By way of example, it can be 500 mPa.s, 550 mPa.s, 600 mPa.s, 650 mPa.s, 700 mPa.s, 745 mPa.s, 850 mPa.s, 960 mPa.s, 1,070 mPa.s, 1,080 mPa.s, 1,090 mPa.s, 1,100 mPa.s, 1,150 mPa.s, 1,200 mPa.s, 1,250 mPa.s, 1,300 mPa.s, 1,350 mPa.s, 1,400 mPa.s, 1,450 mPa.s, 1,500 mPa.s, or any value between the two end values.

[0074] In the present invention, the content of the hydrogen-containing silicone resin is 0.1 to 0.4 parts by weight, and illustratively, it can be 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, or any value in between.

[0075] In the present invention, the Pt content of the platinum catalyst is 0.4-0.5%. For example, it can be 0.4%, 0.45%, 0.5%, or any value between the two end values.

[0076] In the present invention, the content of the platinum catalyst is 0.015 to 0.05 parts by weight, and can be 0.015 parts by weight, 0.02 parts by weight, 0.025 parts by weight, 0.03 parts by weight, 0.035 parts by weight, 0.04 parts by weight, 0.045 parts by weight, 0.05 parts by weight, or any value between the two end values. The addition of conventional platinum catalysts is prone to yellowing of the film under high-temperature curing and baking; the present invention uses the model CSAT-F50050V produced by Jiangxi Beiteli New Materials Co., Ltd., which has no obvious yellowing phenomenon after high-temperature baking, can improve the display color and clarity of the screen for long-term use, and improve the visual experience.

[0077] A diluent may be added to the organic silicon optical adhesive of the present invention to adjust the coating viscosity. The amount of the diluent may be determined according to the required solid content. The amount of the diluent in the present invention may be 40 to 60 parts by weight, such as 40 parts by weight, 41 parts by weight, 42 parts by weight, 45 parts by weight, 47 parts by weight, 48 parts by weight, 50 parts by weight, 52 parts by weight, 54 parts by weight, 55 parts by weight, 57 parts by weight, 60 parts by weight, or any value between the two end values. The specific selection of the diluent may be a conventional diluent, and in the present invention, at least one of cyclohexane and heptane may be selected.

[0078] The present invention also provides a method for preparing an organic silicone optical adhesive, which is specifically as follows: adding each component according to the above ratio into a reaction kettle and fully stirring, the temperature does not exceed 35°C during stirring, and the above organic silicone optical adhesive can be obtained after stirring for 1 to 3 hours.

[0079] The fourth aspect of the present invention provides an application of an organic silicone optical adhesive, wherein the organic silicone optical adhesive described in the third aspect of the present invention is applied to the bonding of a touch display screen.

[0080] The organic silicone optical adhesive of the present invention can be made into a film form for practical application, and the film structure includes a first release film layer, an organic silicone optical adhesive layer and a second release film layer stacked in sequence; wherein the organic silicone optical adhesive layer contains the organic silicone optical adhesive described in the third aspect of the present invention.

[0081] When the organic silicone optical adhesive of the present invention is used for coating, the coating liquid needs to be prepared 60 minutes before coating. First, the components of the organic silicone optical adhesive are mixed evenly, and a diluent (such as cyclohexane) of corresponding weight parts is added according to the coating viscosity and solid content requirements. The mixture is dispersed for about 30 minutes, and the stirring speed is 200-300r / min. Vacuum defoaming treatment is then performed until the coating liquid is free of bubbles under observation of a strong light before coating on the release substrate. During the coating process, a comma scraper type, Lip die (lip film extrusion type) or Slot die (slot die extrusion type) can be used for coating. The thickness of the coated film can be controlled according to actual needs, for example, controlled within 50-1,000μm. After coating, the film can be shaped in an oven (the maximum temperature is set to 150°C and the machine speed is 2-10m / min) to obtain the organic silicone optical adhesive film.

[0082] The organic silicone optical adhesive film obtained by the present invention has excellent optical properties and excellent modulus control, and can improve the bonding clarity of the touch display screen while achieving the effect of low initial bonding peeling force and obvious increase in peeling force after standing for a period of time, which is convenient for timely repair of the adhesive film and solves the problem of delamination and movement between the adhered objects caused by low adhesion of the film product during use after bonding.

[0083] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0084] The experimental methods used in the following examples are conventional methods unless otherwise specified; the reagents, materials, etc. used in the following examples are commercially available unless otherwise specified. 1 g in the following examples represents 1 part by weight.

[0085] Preparation of modified silicone resin

[0086] Preparation Example 1

[0087] ①Composition of modified silicone resin:

[0088] Methyl MQ resin (manufacturer: Chengdu Chenguang Boda New Materials Co., Ltd., model: MSR8803, weight average molecular weight 7,210 g / mol, hydroxyl content 1.61%, M / Q ratio 0.65), 46 g;

[0089] Epoxy modified MQ resin (manufacturer: Hubei Longsheng Sihai New Materials Co., Ltd., model: SH-023-4, epoxy value 0.1%, weight average molecular weight 5,200 g / mol, hydroxyl content 1.0%, M / Q ratio 0.8), 15 g;

[0090] Modifier: 3-mercaptopropyltrimethoxysilane (manufacturer: Zhuoli (Shanghai) Materials Co., Ltd., model: PR-903, mercapto content 7.13%, methoxy content 46.5%), 11.5 g;

[0091] Basic catalyst: tetramethylammonium hydroxide pentahydrate (manufacturer: Aladdin Biochemical Technology Co., Ltd., purity 97%), 0.11 g;

[0092] First solvent: anhydrous ethanol, 0.65g;

[0093] Second solvent: cyclohexane, 27 g.

[0094] ② Preparation method of modified silicone resin:

[0095] The above components are mixed by weight and stirred evenly, and then stirred for 30 minutes using a three-dimensional mixer at a speed of 1600r / min; the mixed solution is then poured into a 150mL three-necked round-bottom flask, heated to about 100°C while passing nitrogen (bubbling 240 times / min) for protection, and the reaction is maintained for about 8 hours until it becomes clear and transparent; the obtained liquid is poured into a rotary evaporator and heated to 160°C, maintained at a vacuum of -0.1MPa for 4 hours, and then cooled and pressurized to room temperature and pressure to obtain a transparent modified silicone resin.

[0096] Preparation Example 2

[0097] The preparation method of this preparation example is the same as that of Preparation Example 1, except that the components and amounts are different, as shown below:

[0098] Methyl MQ resin (manufacturer: Chengdu Chenguang Boda New Materials Co., Ltd., model: MSR8808, weight average molecular weight 6,000 g / mol, hydroxyl content 1.3%, M / Q ratio 0.65), 30 g;

[0099] Epoxy modified MQ resin: SH-023-4, 10g;

[0100] Modifier: 3-mercaptopropyltrimethoxysilane, 8 g;

[0101] Basic catalyst: tetramethylammonium hydroxide pentahydrate, 0.05 g;

[0102] First solvent: anhydrous ethanol, 0.3 g;

[0103] Second solvent: cyclohexane, 20 g.

[0104] Preparation Example 3

[0105] The preparation method of this preparation example is the same as that of Preparation Example 1, except that the components and amounts are different, as shown below:

[0106] Methyl MQ resin (manufacturer: Chengdu Chenguang Boda New Materials Co., Ltd., model: MSR8803, weight average molecular weight 9,000 g / mol, hydroxyl content 2.5%, M / Q ratio 0.65), 60 g;

[0107] Epoxy modified MQ resin: SH-023-4, 20g;

[0108] Modifier: 3-mercaptopropyltrimethoxysilane, 18 g;

[0109] Basic catalyst: tetramethylammonium hydroxide pentahydrate, 0.3 g;

[0110] First solvent: anhydrous ethanol, 1g;

[0111] Second solvent: cyclohexane, 40 g.

[0112] Preparation Example 4

[0113] The preparation method of this preparation example group is the same as that of Preparation Example 1, and is mainly used to prepare the influence of epoxy-modified MQ resins with different epoxy values ​​on modified silicone resins. The difference is that the epoxy values ​​of the epoxy-modified MQ resins are different, and the specific differences are as follows:

[0114] Preparation Example 4-1: Epoxy-modified MQ resin, manufacturer: Hubei Longsheng Sihai New Materials Co., Ltd., model: SH-023-7b, epoxy value is 0.06%, weight average molecular weight is 5,400 g / mol, hydroxyl content is 0.5%, M / Q ratio is 0.8;

[0115] Preparation Example 4-2: Epoxy-modified MQ resin, manufacturer: Hubei Longsheng Sihai New Materials Co., Ltd., model: SH-023-4c, epoxy value is 0.16%, weight average molecular weight is 5,300 g / mol, hydroxyl content is 0.6%, M / Q ratio is 0.7;

[0116] Preparation Example 4-3: Epoxy-modified MQ resin, manufacturer: Hubei Longsheng Sihai New Materials Co., Ltd., model: SH-023-7a, epoxy value is 0.04%, weight average molecular weight is 5,250 g / mol, hydroxyl content is 0.65%, M / Q ratio is 0.75;

[0117] Preparation Example 4-4: Epoxy-modified MQ resin, manufacturer: Hubei Longsheng Sihai New Materials Co., Ltd., model: SH-023-4e, epoxy value is 0.18%, weight average molecular weight is 5,600 g / mol, hydroxyl content is 4%, and M / Q ratio is 0.8.

[0118] Preparation Example 5

[0119] The preparation method of this preparation example is the same as that of Preparation Example 1, and the components do not contain epoxy-modified MQ resin. The composition and amount of the other components are the same as those of Preparation Example 1.

[0120] Preparation Example 6

[0121] The preparation method of this preparation example group is the same as that of Preparation Example 1, and is mainly used to compare the effect of the modifier on the modified silicone resin. The difference lies in the amount and structure of the modifier. The other components and their amounts are the same as those of Preparation Example 1. The specific differences are as follows:

[0122] Preparation Example 6-1: without modifier;

[0123] Preparation Example 6-2: The modifier is an equal amount of methyltriethoxysilane containing only ethoxy groups (manufacturer: Aladdin Reagent Co., Ltd., SKU: T103634-2.5L);

[0124] Preparation Example 6-3: The modifier is an equal amount of methyltrimethoxysilane containing only methoxy groups (manufacturer: Aladdin Reagent Co., Ltd., SKU: T106658-2.5L).

[0125] Preparation of silicone optical adhesive

[0126] Example 1

[0127] ① Composition of silicone optical adhesive:

[0128] Vinyl silicone oil A (manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., model: Andisil VS 5000, viscosity 5,000 mPa.s, vinyl content 0.168%), 20 g;

[0129] Vinyl silicone oil B (manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., model: Andisil VS80000, viscosity 80,000 mPa.s, vinyl content 0.0672%), 35 g;

[0130] 17 g of the modified silicone resin prepared in Preparation Example 1;

[0131] Inhibitor: 2-methyl-3-butyn-2-ol (manufacturer: Aladdin Biochemical Technology Co., Ltd., purity 98%), 0.06 g;

[0132] Double-ended hydrogenated silicone oil (Manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., Model: Andisil CE-500, hydrogen content 0.07%, viscosity 500mm 2 / s), 6g;

[0133] Hydrogenated silicone resin (manufacturer: Shandong Dayi Chemical Co., Ltd., model: HMQ103-0.4%, hydrogen content 0.4%, M / Q ratio 1.3, viscosity 1,150 mPa.s), 0.3 g;

[0134] Platinum catalyst (manufacturer: Jiangxi Beiteli New Materials Co., Ltd., model: CSAT-F50050V, Pt content 0.5%), 0.025 g;

[0135] Cyclohexane, 50 g.

[0136] ② Preparation method of silicone optical adhesive: Add the components into the reaction kettle according to the above ratio and stir them fully. The stirring temperature is maintained above 35°C. After stirring for 2 hours, the silicone optical adhesive can be obtained and it is set aside after vacuum defoaming.

[0137] Example 2

[0138] This example is carried out with reference to Example 1, and its preparation method is the same as that of Example 1, except that the composition of the organic silicone optical adhesive is different, and the specific differences are as follows:

[0139] Vinyl silicone oil A (manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., model: Andisil VS2000, viscosity 2,000 mPa.s, vinyl content 0.12%), 15 g;

[0140] Vinyl silicone oil B (manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., model: Andisil VS50000, viscosity 50,000 mPa.s, vinyl content 0.0672%), 30 g;

[0141] 15 g of the modified silicone resin prepared in Preparation Example 1;

[0142] Inhibitor: 2-methyl-3-butyn-2-ol, 0.02 g;

[0143] Double-ended hydrogenated silicone oil, 3 g;

[0144] Hydrogenated silicone resin (manufacturer: Shandong Dayi Chemical Co., Ltd., model: DY-HMQ211-0.2%, hydrogen content 0.2%, M / Q ratio 1.3, viscosity 650 mPa.s), 0.1 g;

[0145] Platinum catalyst, 0.015 g;

[0146] Cyclohexane, 40.27 g.

[0147] Example 3

[0148] This example is carried out with reference to Example 1, and its preparation method is the same as that of Example 1, except that the composition of the organic silicone optical adhesive is different, and the specific differences are as follows:

[0149] Vinyl silicone oil A (manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., model: Andisil VS10000, viscosity 10,000 mPa.s, vinyl content 0.23%), 25 g;

[0150] Vinyl silicone oil B (manufacturer: Anbia Special Silicone (Nantong) Co., Ltd., model: AndisilVS100000, viscosity 100,000 mPa.s, vinyl content 0.0672%), 40 g;

[0151] 25 g of the modified silicone resin prepared in Preparation Example 1;

[0152] Inhibitor: 2-methyl-3-butyn-2-ol, 0.08 g;

[0153] Double-ended hydrogenated silicone oil, 8g;

[0154] Hydrogenated silicone resin (manufacturer: Shandong Dayi Chemical Co., Ltd., model: HMQ102-0.5%, hydrogen content 0.5%, M / Q ratio 1.2, viscosity 780 mPa.s), 0.4 g;

[0155] Platinum catalyst, 0.05 g;

[0156] Cyclohexane, 62.85 g.

[0157] Example 4

[0158] This example is carried out with reference to Example 1, and its preparation method is the same as that of Example 1, except that an equal amount of the modified silicone resin prepared in Preparation Example 2 is used, and the composition and amount of other components are the same as those in Example 1.

[0159] Example 5

[0160] This example is carried out with reference to Example 1, and its preparation method is the same as that of Example 1, except that an equal amount of the modified silicone resin prepared in Preparation Example 3 is used, and the composition and amount of other components are the same as those in Example 1.

[0161] Example 6 Group

[0162] This example group was prepared with reference to Example 1, and its preparation method was the same as that of Example 1, except that an equal amount of the modified silicone resin prepared in Preparation Example 4 was used, and the other components and amounts were the same as those in Example 1, and the specific differences were as follows:

[0163] Example 6-1: using the modified silicone resin prepared in Preparation Example 4-1;

[0164] Example 6-2: Using the modified silicone resin prepared in Preparation Example 4-2;

[0165] Example 6-3: Using the modified silicone resin prepared in Preparation Example 4-3;

[0166] Example 6-4: Using the modified silicone resin prepared in Preparation Example 4-4.

[0167] Comparative Example 1

[0168] This comparative example was carried out with reference to Example 1, and its preparation method was the same as that of Example 1, except that an equal amount of the modified silicone resin prepared in Preparation Example 5 was used.

[0169] Comparative Example 2

[0170] This comparative example group was prepared with reference to Example 1, and its preparation method was the same as that of Example 1, except that an equal amount of the modified silicone resin prepared in Preparation Example 6 was used, and the composition and amount of other components were the same as those of Example 1, and the specific differences were as follows:

[0171] Comparative Example 2-1: using the modified silicone resin prepared in Preparation Example 6-1;

[0172] Comparative Example 2-2: The modified silicone resin prepared in Preparation Example 6-2 was used.

[0173] Comparative Example 3

[0174] This comparative example was carried out with reference to Example 1, except that the modified silicone resin was not prepared according to the preparation method of the modified silicone resin in Preparation Example 1, but was simply stirred and mixed using a three-dimensional mixer at 1600 r / min for 4 hours.

[0175] Comparative Example 4

[0176] This comparative example group was carried out with reference to Example 1, the only difference being that vinyl silicone oil A or vinyl silicone oil B was not added to the silicone optical adhesive, and in order to maintain the same solid content, the amount of diluent cyclohexane was adjusted, and the specific differences are as follows:

[0177] Comparative Example 4-1: No vinyl silicone oil A was added, and the amount of cyclohexane was 37.24 g;

[0178] Comparative Example 4-2: No vinyl silicone oil B was added, and the amount of cyclohexane used was 27.67 g.

[0179] Comparative Example 5

[0180] This comparative example group was carried out with reference to Example 1, except that the components in the organic silicone optical adhesive were different, and the specific differences are as follows:

[0181] Comparative Example 5-1: No double-terminal hydrogen-containing silicone oil was included, and the amount of cyclohexane used was 46.17 g;

[0182] Comparative Example 5-2: Using an equal amount of conventional hydrogenated silicone oil (manufacturer: Dow Chemical, model: 7028, hydrogen content 1.4%, viscosity 22 mm 2 / s).

[0183] Comparative Example 6

[0184] This comparative example is carried out with reference to Example 1, except that a conventional silicone resin (manufacturer: Shandong Dayi Chemical Co., Ltd., model: DY-MQ102 (0.8) methyl MQ silicone resin) is used instead of the modified silicone resin prepared by the present invention, and the other components and their preparation methods are the same as those in Example 1.

[0185] Test Case

[0186] The organic silicone optical adhesive prepared in the above embodiments and comparative examples is coated into an adhesive film. The specific method is: a comma scraper is used to coat the coating liquid on the release film. After coating, it is dried in an oven (the maximum temperature is set to 150°C and the machine speed is 8m / min) to form an adhesive film. The thickness of the dry adhesive film is 250±10μm. The release film is coated on the adhesive film surface to obtain a test sample. The test sample is tested using the following instruments and methods. The test results are recorded in Tables 1 and 2. Specifically:

[0187] (1) Optical performance test

[0188] The transmittance (%) and haze (%) of the silicone optical adhesive film were tested using a spectrophotometer (CM-3600A) with a full-band transmittance method, and the refractive index (%) was tested using an Abbe refractometer.

[0189] HunterLab UltraScan VIS was used to test L, a, and b values ​​using the transmission method. The present invention mainly focuses on the change of yellow value and b value and records the b value. The optical adhesive requires the transmittance to be greater than 90%, the haze to be ≤0.5%, and the b value to be ≤0.4.

[0190] (2) High and low temperature modulus test

[0191] The storage modulus (KPa) of the silicone optical adhesive film at -30°C, 23°C and 100°C was tested respectively, and the modulus Tanδ at -30°C, 23°C and 100°C was tested respectively using a dynamic mechanical analyzer (DMA-TA) and an oscillating shear method.

[0192] (3) Elongation at break and peel strength test

[0193] According to GB / T 30776-2014 "Test method for tensile strength and elongation at break of adhesive tapes", the elongation at break (%) of silicone optical adhesive films is tested. Generally, the elongation at break is required to be between 1700% and 2500%.

[0194] The glue of each embodiment and comparative example was coated on a 50 μm thick PET substrate, and the other preparation processes were the same as those of the test samples. The samples reinforced with PET were used for the following peel strength test, and the laminated plate was glass. The peel strength (gf / in) was tested at room temperature for 30 minutes (RT / 30min) and at room temperature for 72 hours (RT / 72h) using the 180° peeling method. The peel strength at RT / 30min was more suitable between 300 and 550 gf / in, and the peel strength at RT / 72h needed to be greater than 800 gf / in.

[0195] (4) Test of actual pasting effect and die-cutting effect

[0196] Use a fully automatic laminating machine and vacuum laminating and high-pressure debubbling method to test the bubble abnormality of 1000 pieces of optical organic silicone film under vacuum laminating at room temperature, and record the bubble abnormality rate (%);

[0197] Use an aging test machine and a high temperature and high humidity simulated environmental aging method to test the bubble rebound of 1000 pieces of optical organic silicone film under D85 aging test for 960 hours, and record the bubble rebound rate (%);

[0198] Using a flat-knife die-cutting machine and a continuous moving square die-cutting method, test 1000 pieces of optical silicone film for die-cutting glue overflow and die-cutting glue pulling abnormalities, and record the die-cutting abnormality rate (%).

[0199] Table 1 Performance test results of various embodiments

[0200]

[0201]

[0202] Table 2 Performance test results of each comparative example

[0203]

[0204] From the test results of Table 1 and Table 2, it can be seen that the silicone optical adhesive prepared by the modified silicone resin provided by the present invention has good optical properties, a low b value, and good yellowing resistance; the storage modulus changes little at low temperature, room temperature and high temperature, has good elongation at break, and can achieve the characteristics of low initial peeling force and high later climbing force, which is convenient for timely repair in practical applications, so that it has excellent solid pasting effect and die-cutting effect.

[0205] The test results of Example 6 show that when epoxy-modified MQ resins with different epoxy values ​​are used to prepare modified silicone resins, when the epoxy value is low, the probability of glue pulling during film die-cutting due to low modulus reaches an unacceptable 0.5%, and the peeling force attenuates. When the epoxy value is high, the probability of bonding bubbles during film bonding due to high modulus reaches an unacceptable 0.5%.

[0206] The test results of comparative example 1 show that when epoxy-modified MQ resin is not added, its elongation at break and peel strength are significantly reduced, and die-cutting has defects such as glue overflow and glue pulling. This is because after lamination, some epoxy groups are missing to form chemical bonds with the active groups on the surface of the adhered object, and the active groups inside the colloid are also reduced, resulting in reduced colloid strength and glue pulling during die-cutting.

[0207] The test results of Comparative Example 2 show that when there is no modifier or only a modifier composed of methoxy or ethoxy, the prepared organic silicone optical adhesive has low transmittance and high haze, resulting in abnormal optical properties and cannot be used normally. This is because the methyl MQ resin and epoxy resin do not have a modifier to participate in the reaction to improve their compatibility with vinyl silicone oil, resulting in a decrease in compatibility and affecting light transmittance.

[0208] The test results of comparative example 3 show that when the modified silicone resin is prepared by simple stirring, its optical properties are reduced and the b value is high, indicating that it is not resistant to yellowing, the storage modulus increases at each temperature, the elongation at break decreases, and bubbles and poor rebound occur after lamination. This is because the grafting rate of the modifier and the resin hydroxyl group is reduced, resulting in reduced compatibility of the resin and abnormal optical properties; at the same time, the modifier participates in the reaction of the vinyl silicone oil and hydrogen silicone oil added later, resulting in an increase in the colloidal modulus and abnormal bubbles during the lamination process.

[0209] The test results of Comparative Example 4 show that when only one vinyl silicone oil is added to the silicone optical adhesive, its storage modulus increases, the elongation at break decreases, and there are bubbles in the bonding and poor rebound. This is because the single-component vinyl silicone oil has an excessive orderly cross-linking reaction, which causes the colloid to form a dense structure, affecting the formation of the colloid winding structure.

[0210] The test results of Comparative Example 5 show that the elongation at break of the prepared silicone optical adhesive is significantly reduced when only conventional end-side hydrogenated silicone oil is used in the silicone optical adhesive, and bubbles and poor rebound are present during bonding. This is because the end-side hydrogenated silicone oil mainly causes the colloid to react to form a dense elastomer, which greatly reduces the viscosity of the colloid. When no double-end hydrogenated silicone oil is present, the storage modulus decreases, the elongation at break decreases, and there are abnormal bubbles.

[0211] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified silicone resin, characterized in that: The invention comprises the following components: methyl MQ resin, epoxy modified MQ resin, a modifier, a basic catalyst, a first solvent and a second solvent; Wherein, the M / Q ratio of the methyl MQ resin is 0.55 to 0.75, and the M / Q ratio of the epoxy modified MQ resin is 0.7 to 0.9; The epoxy value of the epoxy-modified MQ resin is 0.06 to 0.16%; The modifier is an organic silicon compound containing a mercapto group and an alkoxy group.

2. The modified silicone resin according to claim 1, characterized in that In parts by weight, the proportions of the components in the modified silicone resin are as follows:

3. The modified silicone resin according to claim 1 or 2, characterized in that: The weight average molecular weight of the methyl MQ resin is 6,000 to 9,000 g / mol, and the hydroxyl content of the methyl MQ resin is 1.3 to 2.5%; And / or, the weight average molecular weight of the epoxy-modified MQ resin is 4,000 to 7,000 g / mol, and the hydroxyl content of the epoxy-modified MQ resin is 0.3 to 1%.

4. The modified silicone resin according to claim 1 or 2, characterized in that: The content of the mercapto group in the modifier is 5.5-8.7%, and the content of the alkoxy group in the modifier is 22.36-49.47%; And / or, the alkoxy group includes one or both of a methoxy group and an ethoxy group.

5. The modified silicone resin according to claim 4, characterized in that: The modifier includes at least one of 3-mercaptopropyltrimethoxysilane, 11-mercaptoundecyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, and γ-mercaptopropyltriethoxysilane; And / or, the alkaline catalyst includes at least one of tetramethylammonium hydroxide pentahydrate and potassium hydroxide; And / or, the first solvent includes at least one of anhydrous ethanol, methanol, and isopropanol, and the second solvent includes at least one of cyclohexane, heptane, and octane.

6. A method for preparing the modified silicone resin according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: The methyl MQ resin, the epoxy modified MQ resin, the modifier, the alkaline catalyst, the first solvent and the second solvent are uniformly mixed according to the above ratio; after nitrogen is introduced, the mixture is heated to 80-120° C. and maintained for 6-10 hours until it reacts to a transparent liquid; the transparent liquid is rotary evaporated at 140-180° C. and a vacuum pressure of -0.1 MPa to -0.05 MPa for 2-6 hours, and the temperature is reduced and the pressure is increased to normal temperature and pressure to obtain the modified silicone resin.

7. An organic silicone optical adhesive, characterized in that: In parts by weight, it includes the following components: Wherein, the modified silicone resin is the modified silicone resin according to any one of claims 1 to 5 or the modified silicone resin prepared by the method according to claim 6.

8. The organic silicone optical adhesive according to claim 7, characterized in that: The viscosity of the vinyl silicone oil A is 2,000 to 10,000 mPa.s, and the viscosity of the vinyl silicone oil B is 50,000 to 100,000 mPa.s; And / or, the vinyl content of the vinyl silicone oil A is 0.12-0.23%, and the vinyl content of the vinyl silicone oil B is 0.03-0.07%.

9. The organic silicon optical adhesive according to claim 7, characterized in that: The hydrogen content of the double-ended hydrogen-containing silicone oil is 0.04-0.08%, and the hydrogen content of the hydrogen-containing silicone resin is 0.2-0.5%; and / or, the M / Q ratio of the hydrogenated silicone resin is 1.2 to 1.5; And / or, the viscosity of the double-ended hydrogenated silicone oil is 300-700 mm 2 / s, the viscosity of the hydrogen-containing silicone resin is 500 to 1,500 mPa.s; and / or, the inhibitor comprises at least one of a vinyl ring body, an alkynol, and diallyl maleate; And / or, the Pt content of the platinum catalyst is 0.4-0.5%.

10. The organic silicon optical adhesive according to any one of claims 7 to 9, used for bonding touch display screens.

Citation Information

Patent Citations

  • Solvent-free organic silicon pressure-sensitive adhesive and preparation method thereof

    CN102174309A

  • Optical joint sealant as well as preparation method and application thereof

    CN112592692A

  • UV (ultraviolet) blocking type organic silicon OCR (optical clear adhesive) as well as preparation method and application thereof

    CN116515453A

  • Transparent organic silicon optical cement with low viscosity and low dielectric constant and preparation method thereof

    CN117247766A

  • Organopolysiloxane, and curable composition comprising the same and manufacturing method for the same

    JP2011021078A